Entre transgressões e consensos : a relação entre ética e estética no caso da telenovela “Lado a Lado” no âmbito do debate sobre ações afirmativas no ano de 2012 - Lopes, Ana Carolina Siani (2017)
This paper aimed to understand the potential relationships between the telenovela "Side by Side" (Rede Globo, 2012) and the clashes and discussions about Affirmative Actions that occurred in the Brazilian media in the year 2012, driven by the judgment of the Supreme Federal Court (STF) on the unconstitutionality of the system of racial quotas, applied by the University of Brasília (Unb) and the target of a lawsuit filed by the Democratic Party (DEM). In this way, the research sought to understand to what extent the novel and its discourse could be related and reverberating the voices of this debate, since it had as its narrative axis the post-abolition period of slavery and the conflicts about the insertion of the black population In the class society of the early twentieth century; period well remembered in the media debate to highlight the historical prejudice and the systematic marginalization of black people in Brazil. Thus, we start from the hypothesis that in both life and art discourses were produced about racism and the racial inequalities of Brazilian society. As a theoretical foundation for the constitution of such understanding, we anchor ourselves in the studies of the Circle of Mikhail Bakhtin (BAKHTIN, 2009; BAKHTIN, 2010; BAKHTIN, 2011; VOLOCHINOV, 2013; BAKHTIN, 2014), establishing a dialogue with The perspective of Cultural Studies on the media (MARTÍN-BARBERO, 1997; KELLNER, STAM, 2010; HALL, 2010; NEWCOMB, 2010), which gave us conditions to think mass communication in its dialogical character and as a terrain Confronted by both hegemonic values and dissenting values. In order to understand the statements produced in "Side by Side" (Rede Globo, 2012) in relation to the mediatic statements of the discussion on racial quotas in 2012, we have taken the text as a methodological path (BAKHTIN, 2011), in order to understand the statements produced in "Lado a Lado" (Rede Globo, 2012) in relation to the mediatic statements of the discussion on racial quotas in 2012, considering the responsiveness of the telenovela as a statement and considering it as a work of art that takes on meaning in its relation with the broader extra-verbal dimension (VOLOCHINOV, 2013). In this way, we seek the reconstitution of the ideological threads of the discourse on racial inclusion in the telenovela, in order to understand how these can constitute a consensus or transgression in relation to the conflicts of life.